Gulf Cooperation Council (GCC) sebagai Organisasi Antar-Pemerintah Regional di Kawasan Teluk Persia dalam Menangani Krisis Diplomasi Qatar-Arab Saudi - Annisa Noor Azizah (Journal of International Relations Diponegoro, 2023)
ABSTRACTThe diplomatic crisis between Qatar and Saudi Arabia in 2017 had a significant impact on relation and regional stability in the Persian Gulf. Saudi Arabia, UAE, and Bahrain severed diplomatic relations with Qatar by withdrawing their ambassadors from Doha, imposing an embargo, and blockading Qatar's territory. This internal dispute was considered to be the worst dispute in Gulf Cooperation Council (GCC) defence and security history. In the midst of a crisis like this, the GCC, as a regional intergovernmental organization in Persian Gulf, should have a certain role and influence to improve relations and maintain regional stability. The purpose of this research is to analyse GCC’s role and influence in the Qatar-Saudi diplomatic crisis. The author will use Clive Archer's institutional liberalism which defines the roles of international organizations as arena, instrument, or actor. The qualitative data used in this research was obtained from journals, books, websites, and documentations or official statements from the GCC and the parties. The results of this research indicate that GCC’s role was a tool or instrument used by its member countries to carry out foreign policy and achieve their respective national interest. Key words: Diplomatic Crisis, Qatar, Saudi Arabia, Gulf Cooperation Council (GCC), Institutional Liberalism